Analysis of Environmental Vibrations in Suburban Railways Affected by Adjacent Bidirectional Tunnels - Dong Li; Zhimin Li; Hongkai Wang; Jili Yin; Zhoujian You; Futong Wang (Applied Sciences)
Train-induced environmental vibrations are a common issue in urban rail transit systems, particularly in suburban railways operating at high speeds, where the impact of these vibrations is more pronounced. This presents significant challenges for urban planners and engineers. Existing research has mainly focused on the impact of single tunnel structures on ground vibrations, with limited understanding of the vibration propagation characteristics of adjacent bidirectional tunnels. To address this gap in knowledge, this study investigates the ground vibration attenuation characteristics induced by train operations in the underground sections of suburban railways, with a focus on the amplification effects of adjacent tunnels on ground vibrations. The results show that the vibrations induced by the trains are concentrated in the 20–50 Hz frequency range and exhibit similar characteristics in all directions. The maximum vertical vibration acceleration and peak acceleration occur directly above the train tunnel. Additionally, adjacent tunnels significantly amplify the maximum peak acceleration at measurement points in directions perpendicular to the track, including both horizontal and vertical directions. Furthermore, the soil within the adjacent tunnels also exhibits amplification of the vertical power spectral amplitude in the 40–100 Hz frequency range. The findings of this study provide new insights into the influence of adjacent bidirectional tunnels on environmental vibrations in suburban railway operations. These results are of significant importance for optimizing railway design and vibration mitigation measures.